The Effect of a STEM-Integrated Project-Based Learning Science E-Module on Students’ Critical Thinking and Problem-Solving Skills - Zulkarnaen; Rahayu, Satutik; Artayasa, I Putu (Journal of Authentic Research, 2025)
Innovation in science learning is essential to meet 21st-century skill demands and support the achievement of the Education for Sustainable Development Goals (ESDGs). This study aims to analyze the effect of a Project-Based Learning (PjBL)-based Science E-Module integrated with the Science, Technology, Engineering, and Mathematics (STEM) approach on students’ critical thinking and problem-solving skills. A quasi-experimental design with a posttest-only control group was employed. The sample consisted of 71 students divided into an experimental group (n = 35), which used the PjBL-STEM E-Module, and a control group (n = 36), which received conventional instruction. Research instruments included tests of critical thinking (CTS) and problem-solving skills (PSS). The assumptions of multivariate normality (Shapiro–Wilk), homogeneity of variance–covariance matrices (Box’s M), and multicollinearity were all met. The MANOVA results revealed a significant simultaneous effect of the treatment on CTS and PSS (p < 0.001). Further univariate tests indicated significant partial effects on CTS (p < 0.001) and PSS (p < 0.001). The mean scores of CTS (Experimental = 80.91; Control = 57.67) and PSS (Experimental = 82.74; Control = 58.47) were significantly higher in the experimental group. Therefore, the STEM-integrated PjBL Science E-Module is effective in improving students’ critical thinking and problem-solving skills. This finding demonstrates that the module serves as a pedagogical innovation aligned with the ESDGs framework and the competencies required for 21st-century education.